2018
DOI: 10.1186/s12906-018-2130-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of depression with Chai Hu Shu Gan San: a systematic review and meta-analysis of 42 randomized controlled trials

Abstract: BackgroundDepression is a common mental disorder. Chai Hu Shu Gan San, a traditional Chinese medicine, is used to treat depression empirically. We present a systematic review and meta-analysis of the therapeutic efficacy and safety of Chai Hu Shu Gan San in treating depression.MethodsSeveral databases, including PubMed, China National Knowledge Internet, Wanfang, Chongqing VIP, and the Cochrane library, were systematically searched from their date of foundation to January 1, 2017. In this review, wehave includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…It is estimated that up to 80% of the population in developing countries use traditional herbs for primary health care [15]. CSS or coadministration of CSS and FLU is commonly used to enhance antidepressant effect and reduce side effects in Chinese clinics [16], which was confirmed by multiple studies [17][18][19]. Chaihu Shugan San (CSS) is a classic and effective antidepressant Chinese herbal medicine that has been used in China for thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that up to 80% of the population in developing countries use traditional herbs for primary health care [15]. CSS or coadministration of CSS and FLU is commonly used to enhance antidepressant effect and reduce side effects in Chinese clinics [16], which was confirmed by multiple studies [17][18][19]. Chaihu Shugan San (CSS) is a classic and effective antidepressant Chinese herbal medicine that has been used in China for thousands of years.…”
Section: Introductionmentioning
confidence: 99%
“…Although the antidepressant mechanism of different responses to CSGS treatment has been extensively investigated, these studies are mainly focused on hippocampal 5-HT receptor and brain-derived neurotrophic factor (BDNF) either at pre-or post-treated CSGS that correlates with therapeutic outcomes [16][17][18]. Herein, we paid more attention to the overall hippocampal metabolism after CGSG and the combined oral administration broad-spectrum antibiotic treatment and then conducted analyses by the UPLC-Q-TOF/MS-based metabolomics approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also found that TCM physicians did not use some antidepressant TCM formulae that have proven useful in clinical trials. For example, a systematic review and meta-analysis study found that Chai-Hu-Shu-Gan-San can effectively reduce the severity and frequency of depression [26]. However, Taiwanese TCM physicians rarely use it to treat patients with depressive prostate cancer.…”
Section: Discussionmentioning
confidence: 99%